A Plasma Circular RNA Profile Differentiates Subjects with Alzheimer’s Disease and Mild Cognitive Impairment from Healthy Controls - Piscopo, Paola; Manzini, Valeria; Rivabene, Roberto; Crestini, Alessio; Le Pera, Loredana; Pizzi, Elisabetta; Veroni, Caterina; Talarico, Giuseppina; Peconi, Martina; Castellano, Anna Elisa; D’Alessio, Carmelo; Bruno, Giuseppe; et al. (International journal of molecular sciences, 2022)
The most frequently used biomarkers to support the diagnosis of Alzheimer’s Disease (AD) are Aβ42, total-Tau, and phospho-tau protein levels in CSF. Moreover, magnetic resonance imaging is used to assess hippocampal atrophy, 18F-FDG PET to identify abnormal brain metabolism, and PET imaging for amyloid deposition. These tests are rather complex and invasive and not easily applicable to clinical practice. Circulating non-coding RNAs, which are inherently stable and easy to manage, have been reported as promising biomarkers for central nervous system conditions. Recently, circular RNAs (circRNAs) as a novel class of ncRNAs have gained attention. We carried out a pilot study on five participants with AD and five healthy controls (HC) investigating circRNAs by Arraystar Human Circular RNA Microarray V2.0. Among them, 26 circRNAs were differentially expressed (FC ≥ 1.5, p < 0.05) in participants with AD compared to HC. From a top 10 of differentially expressed circRNAs, a validation study was carried out on four up-regulated (hsa_circRNA_050263, hsa_circRNA_403959, hsa_circRNA_003022, hsa_circRNA_100837) and two down-regulated (hsa_circRNA_102049, hsa_circRNA_102619) circRNAs in a larger population. Moreover, five subjects with mild cognitive impairment (MCI) were investigated. The analysis confirmed the upregulation of hsa_circRNA_050263, hsa_circRNA_403959, and hsa_circRNA_003022 both in subjects with AD and in MCI compared to HCs. We also investigated all microRNAs potentially interacting with the studied circRNAs. The GO enrichment analysis shows they are involved in the development of the nervous system, and in the cellular response to nerve growth factor stimuli, protein phosphorylation, apoptotic processes, and inflammation pathways, all of which are processes related to the pathology of AD.